Workshop in Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The lower and upper regions of the CCAFS Nyando site are located in western Kenya near Lake Victoria. This site is comprised of two tribes and two main agro-ecological regions. The Luo, traditionally a fishing tribe, live in lower Nyando, which is characterized by soil erosion and lower agricultural production. The Kalenjin live in upper Nyando and have more rainfall and higher productivity. This was investigated during Novermber of last year, when a team of researchers went into Nyando and conducted some participatory research workshop activities. Photo: A. Eitzinger (CIAT)